2017
DOI: 10.18295/squmj.2016.17.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Decision-to-Delivery Time Intervals in Emergency Caesarean Section Cases: Repeated cross-sectional study from Oman

Abstract: abstract:Objectives: In cases of fetal intolerance to labour, meeting the standard decision-to-delivery time interval (DDI) of ≤30 minutes is challenging. This study aimed to assess DDIs in emergency Caesarean section (CS) cases to identify factors causing DDI delays and the impact of a delayed DDI on perinatal outcomes. Methods: This repeated cross-sectional study included all emergency CS procedures performed due to acute fetal distress, antepartum haemorrhage or umbilical cord prolapse at the Nizwa Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 12 publications
1
17
1
Order By: Relevance
“…The difference might be due to sample size. Another study done in Oman concluded that a DDI below 30 min was achieved in 23.8% of category-1 emergency C/S [22] which is comparable with the current study. On the other hand, a study done in Benin teaching hospital has showed that a DDI below 30 min was achieved in only 5.7% of emergency C/S and the mean ± SD of DDI was 106.3 ± 79.5 min [23].…”
Section: Discussionsupporting
confidence: 90%
“…The difference might be due to sample size. Another study done in Oman concluded that a DDI below 30 min was achieved in 23.8% of category-1 emergency C/S [22] which is comparable with the current study. On the other hand, a study done in Benin teaching hospital has showed that a DDI below 30 min was achieved in only 5.7% of emergency C/S and the mean ± SD of DDI was 106.3 ± 79.5 min [23].…”
Section: Discussionsupporting
confidence: 90%
“…In Oman and Ethiopia for instance the rates are around 20-25%. 11,12 whereas in Hong Kong and Singapore rates as high as 80-90% are reported. 13,14 In order to ensure only 'genuine' category 1 cesarean sections were included, case files were reviewed to ensure the indication warranted a category 1 procedure.…”
Section: Discussionmentioning
confidence: 98%
“… 19 But the result was lower than a study conducted in Oman showing that in 23.8% of emergency CS deliveries, a DDI less than 30 minutes was achieved. 20 …”
Section: Discussionmentioning
confidence: 99%